COASTAL STAIRCASE SEQUENCES REFLECTING SEA-LEVEL OSCILLATIONS AND TECTONIC UPLIFT DURING THE QUATERNARY AND NEOGENE - Pedoja K.; Husson L.; Johnson M.E.; Melnick D.; Witt C.; Pochat S.; Nexer M.; Delcaillau B.; Pinegina T.K.; Poprawski Y.; Authemayou C.; Elliot M.; et al. (My University, 2014)
Many coasts feature sequences of Quaternary and Neogene shorelines that are shaped by a combination of sealevel oscillations and tectonics.We compiled a global synthesis of sea-level changes for the following highstands: MIS 1, MIS 3, MIS 5e and MIS 11. Also, we date the apparent onset of sequences of paleoshorelines either from published data or tentatively extrapolating an age for the uppermost, purported oldest shoreline in each sequence. Including themost documentedMIS 5e benchmark, weidentify 926 sequences out ofwhich 185 also feature Holocene shorelines. Six areas are identified where elevations of the MIS 3 shorelines are known, and 31 feature elevation data for MIS 11 shorelines. Genetic relationships to regional geodynamics are further explored based on the elevations of the MIS 5e benchmark. Mean apparent uplift rates range from 0.01 ± 0.01 mm/yr (hotspots) to 1.47 ± 0.08 mm/yr (continental collision). Passive margins appear as ubiquitously uplifting, while tectonic segmentation is more important on active margins. From the literature and our extrapolations, we infer ages for the onset of formation for ~180 coastal sequences. Sea level fingerprinting on coastal sequences started at least during mid Miocene and locally as early as Eocene.Whether due to the changes in the bulk volume of seawater or to the temporal variations in the shape of ocean basins, estimates of eustasy fail to explain the magnitude of the apparent sea level drop. Thus, vertical ground motion is invoked, and we interpret the longlasting development of those paleoshore sequences as the imprint of glacial cycles on globally uplifted margins in response to continental compression. The geomorphological expression of the sequences matches the amplitude and frequency of glacial cyclicity. Frommiddle Pleistocene to present-day, moderately fast (100,000 yrs) oscillating sea levels favor the development of well identified strandlines that are distinct from one another. Pliocene and Lower Pleistocene strandlines associated with faster cyclicity (40,000 yrs) are more compact and easily merge into rasas, whereas older Cenozoic low-frequency eustatic changes generally led to widespread flat-lying coastal plains.
Keywords: 38.17.91 Региональная тектоника